Active Learning Based on Educational Games in Increasing Students Interest in Learning at SDN 28 in Bima City - Daniah, Ainun Rahma; Masitha, Dewi; Fuaddudin, Fuaddudin (Prodi PAI STIT Sunan Giri Bima, 2025)
This study aims to describe the application of active learning methods based on educational games in increasing the learning interest of second-grade students at SDN 28 Melayu Kota Bima. The background of this study stems from the low learning motivation of students caused by the use of monotonous and less interactive learning strategies. This study employs a qualitative approach with a case study design, utilizing data collection techniques such as observation, interviews, and documentation. The results indicate that educational games can create a fun and engaging learning environment, increase student active participation, and foster positive interaction between teachers and students. Activities such as interactive quizzes, card games, and group work help students become more focused and enthusiastic in their learning. This approach is also tailored to students' diverse learning styles and needs, thereby creating a more inclusive learning process. Thus, active learning through educational games has proven to be an effective and practical strategy in increasing students' interest in learning at the elementary school level.